A Sociological Analysis of Telemedicine, Patients, and Healthcare Professionals' Responsibilities in the Digital Health Era - Nur Endah Sri Ningsih; Tinuk Dwi Cahyani; Haris Tofly (Journal Informatic, Education and Management (JIEM), 2026)
Development of digital technology in healthcare driven the emergence of telemedicine practices as an alternative for remote healthcare services. However, this progress presents complex legal and social challenges, particularly concerning the protection of patient rights and the responsibilities of healthcare providers. This article examines the urgency of regulating telemedicine within the context of patient law and the responsibilities of healthcare providers through the lens of sociology. The method used is normative juridical. According to Law Number 17 of 2023 concerning technology-based healthcare services, this law provides a foundation for telemedicine and the information technology in healthcare services, establishing guidelines for the practice of remote healthcare services. Law Number 17 of 2023 aims to address increasingly complex health challenges in Indonesia with a more modern and technology-based approach. This aligns with the evolving needs of society, especially following the experiences of the COVID-19 pandemic. Therefore, there is a need for adaptive regulatory updates and increased digital literacy among the public to support a fair and sustainable healthcare system.